2020
DOI: 10.1038/s41598-020-61732-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of voice perception is dissociated across gender cues in school-age children

Abstract: Children's ability to distinguish speakers' voices continues to develop throughout childhood, yet it remains unclear how children's sensitivity to voice cues, such as differences in speakers' gender, develops over time. This so-called voice gender is primarily characterized by speakers' mean fundamental frequency (F0), related to glottal pulse rate, and vocal-tract length (VTL), related to speakers' size. Here we show that children's acquisition of adult-like performance for discrimination, a lower-order perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(87 citation statements)
references
References 56 publications
(81 reference statements)
6
46
0
Order By: Relevance
“…The results showed that similarly to F0 differences, young children did not benefit from differences in speakers' VTL only, but they did benefit from a change in the two voice cues together, although this benefit was still lower than that observed in older children. This argument is also in line with the results of our previous study that indicate children weigh both F0 and VTL cues to categorize speakers' voice gender (Nagels et al, 2020a). Children may also not be sensitive enough to the acoustic variations induced by only mean F0 or only VTL differences to benefit from these during speech stream segregation and could have been relying on additional acoustic differences for speech segregation in the aforementioned studies by Leibold et al (2018) and Wightman and Kistler (2005).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results showed that similarly to F0 differences, young children did not benefit from differences in speakers' VTL only, but they did benefit from a change in the two voice cues together, although this benefit was still lower than that observed in older children. This argument is also in line with the results of our previous study that indicate children weigh both F0 and VTL cues to categorize speakers' voice gender (Nagels et al, 2020a). Children may also not be sensitive enough to the acoustic variations induced by only mean F0 or only VTL differences to benefit from these during speech stream segregation and could have been relying on additional acoustic differences for speech segregation in the aforementioned studies by Leibold et al (2018) and Wightman and Kistler (2005).…”
Section: Introductionsupporting
confidence: 88%
“…For instance, the ability to segregate different speech streams based on differences in speakers' voice characteristics may help with optimally using attentional mechanisms for understanding the target speech signal better. As the ability to discriminate subtle differences in voice cues seems to develop in children during the school-age years (Buss et al, 2017a;Cleary et al, 2005;Flaherty et al, 2019;Nagels et al, 2020a), their ability to benefit from voice differences between target and masker speakers for perceiving speech in competing speech may be limited, potentially affecting further processing stages.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in line with previous findings that NH children's ability to recognize vocal emotions improves gradually as a function of age (Tonks et al, 2007;Sauter, Panattoni & Happé, 2013). It may be that children require more auditory experience to form robust representations of vocal emotions or rely on different acoustic cues than adults, as was shown in research on the development of sensitivity to voice cues (Mann, Diamond & Carey, 1979;Nittrouer & Miller, 1997;Nagels et al, 2020). It is still unclear on which specific acoustic cues children are basing their decisions on and how this differs from adults.…”
Section: Discussion Age Effectsupporting
confidence: 91%
“…NH and CI children were tested in a quiet room at their home, and NH adults were tested in a quiet testing room at the two universities. Since the present experiment was part of a larger project on voice and speech perception (Perception of Indexical Cues in Kids and Adults (PICKA)), data were collected from the same population of children and adults in multiple experiments, see, for instance, Nagels et al (2020). The experiment started with a training session consisting of 4 practice stimuli and was followed by the test session consisting of 36 experimental stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…[34][35][36]). Despite this cultural and individual variation, listeners are highly sensitive to the distinction between male and female voices, a skill that arises early but continues to develop throughout one's lifetime [37]. Evidence from auditory Stroop tasks with male and female voices shows that people automatically process the speaker's gender even when this information is task irrelevant [38].…”
Section: The Frequency Code (A) Backgroundmentioning
confidence: 99%